China's initiative "One way, one belt" and prospects of bilateral cooperation (Journal of Oriental Studies, 2016)
In this article there are considered such recent initiatives as putting up "United constructing of Silk Way economic zone", "One zone one way", "Investigation bank of Asian infrastructure" by President of China. The President of Kazakhstan Nursultan Nazarbayev's "2050 strategy" and "Bright way is a way leading to the future" strategies' important aspect is development of infrastructure, therefore there are a lot of mutual appropriate angles. The Chinese side is ready to investigate a great sum to materialize their own initiatives. Therefore, two bilateral unity relationship's big development future is described.
Keywords: Initiative; "Silk Way"; "One zone one way"; "Bright way"; unity; development